2004
DOI: 10.1002/ijc.20570
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and significance of prion protein in gastric cancer and multidrug‐resistant gastric carcinoma cell line SGC7901/ADR

Abstract: In our previous work, cellular prion protein (PrPc) was identified as an upregulated gene in adriamycin-resistant gastric carcinoma cell line SGC7901/ADR compared to its parental cell line SGC7901. Here we investigate the expression of PrPc in gastric cancer and whether it was involved in multidrug resistance (MDR) of gastric cancer. We demonstrated that PrPc was ubiquitously expressed in gastric cancer cell lines and tissues. PrPc conferred resistance of both P-glycoprotein (P-gp)-related and P-gp-nonrelated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 29 publications
7
102
2
Order By: Relevance
“…For example, tumor resistance to TNFa has been associated with increased PrP C expression. 17 PrP C levels have also been found to be up-regulated in adriamycin-resistant gastric carcinoma, 18 with suppression of PrP C partially reversing this phenotype in gastric and breast carcinoma cells. 18 PrP C overexpression in gastric tumor cell lines has also been associated with increased expression of Bcl-2, and decreased expression of p53 and Bax, indicating a possible increase in resistance to programmed cell death.…”
Section: Uiccmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, tumor resistance to TNFa has been associated with increased PrP C expression. 17 PrP C levels have also been found to be up-regulated in adriamycin-resistant gastric carcinoma, 18 with suppression of PrP C partially reversing this phenotype in gastric and breast carcinoma cells. 18 PrP C overexpression in gastric tumor cell lines has also been associated with increased expression of Bcl-2, and decreased expression of p53 and Bax, indicating a possible increase in resistance to programmed cell death.…”
Section: Uiccmentioning
confidence: 99%
“…17 PrP C levels have also been found to be up-regulated in adriamycin-resistant gastric carcinoma, 18 with suppression of PrP C partially reversing this phenotype in gastric and breast carcinoma cells. 18 PrP C overexpression in gastric tumor cell lines has also been associated with increased expression of Bcl-2, and decreased expression of p53 and Bax, indicating a possible increase in resistance to programmed cell death. [18][19][20] In the absence of PrP C expression, resistance to TRAIL-induced apoptosis was inhibited in breast adriamycinresistant carcinoma cells.…”
Section: Uiccmentioning
confidence: 99%
“…Conversely, we recently established that PrP c overexpression led to an increased staurosporine-evoked cell death (13) in transfected or inducible cell lines and showed that this cellular response was associated with an activation of caspase-3 linked to a transcriptional and post-transcriptional control of the p53 transcription factor (14). Moreover, we and others have described that down-regulation of PrP c in cell lines (14,15) or deletion in vivo decreased p53 expression (14,16). This last observation would plead for a p53-dependent proapoptotic function of PrP c rather than a protective one given the pivotal role of this tumor suppressor in triggering cell death.…”
mentioning
confidence: 93%
“…Previous studies notified that the mutation of Mdr-1 gene could upregulate the p-glycoprotein expression and PKC-mediated phosphorylation and other associated proteins could directly modify the p-glycoprotein function. [25][26][27][28] Studies are underway to investigate whether Bicyclol affects those correlated mechanisms for reducing p-glycoprotein expression and mediated MDR in both Vin R KB and Adr R MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%